Birthweight and Apgar at 5 minutes of life for the prediction of severe neonatal outcomes in preterm prelabor rupture of membranes. (2nd December 2022) - Duncan, Jose R.; Sawangkum, Peeraya; Hoover, Elizabeth A.; Aziz, Michael M.; Vilchez, Gustavo
Abstract: Objective: The aim of our study was to investigate the predictive accuracy of clinical variables available after delivery for severe neonatal outcomes (SNO) in pregnancies complicated by PPROM. Materials and methods: This was a secondary analysis of a prospective cohort of pregnancies complicated by PPROM. We included expectant mothers from 13–46 years of age who were between 23 and 36 6/7 weeks of gestation. We excluded multiple gestations, complex fetal anomalies, those with fetal demise and outborn infants. Our primary outcome was a composite of SNO (respiratory distress syndrome, necrotizing enterocolitis, Intra-ventricular hemorrhage, sepsis, and death). The variables assessed where gestational age at delivery, birthweight, Apgar score at 5 min of life, Apgar <7 at 5 min of life, small for gestational age, sex, umbilical artery pH, and mode of delivery. Logistic regression was performed to evaluate the predictive accuracy of each of these variables. Stepwise multivariable logistic regression was utilized to assess the effect of variables with univariate analysis p value <.10 and those baseline characteristics with a statistically significant association with our composite score. Results: We included 108 infants. SNO was diagnosed in 44 (41%) neonates. The Apgar score at 5 min (AUC = 0.89; p = <.001), the birthweight (AUC = 0.88; p = <.001), gestational age at delivery (AUC = 0.87; p = <.001), and the Apgar score < 7 at 5 min (AUC = 0.73; p = <0.001) were statistical significant predictors of SNO. Sex ( p =.15), mode of delivery ( p =.15), umbilical artery Ph ( p =.28), SGA ( p =.85) were not statistically significant predictors of SNO. After stepwise multivariable logistic regression only the Apgar at 5 min and birth weight remained statistically significant predictors for SNO (AUC = 0.94). Conclusions: In pregnancies complicated by PPROM the birthweight and the Apgar at 5 min of life are accurate predictors of a composite score of SNO. We acknowledge the need for larger and more diverse studies to corroborate our findings. Brief rationale: We assessed the predictive accuracy of clinical variables available after delivery for severe neonatal outcomes in pregnancies complicated by PPROM. We found that the birthweight and the Apgar score at 5 min were accurate predictors of such outcomes in this population. Our results may aid providers in the counseling of premature infants born after PPROM.